(untitled) (Applied Biological Research, 2016)
The present study was aimed to assess the influence of strobilurin fungicides on non-fungicidal physiological characters viz.,root length, plant height, number of branches, leaf area and total dry matter accumulation in chilli (Capsicum annum). The experiment was laid out in a randomized block design and comprised of seven treatments of various concentrations of strobulin fungicides trifloxystrobin and tebuconazole. The plant height was significantly reduced in all the strobilurin fungicidal treatments as compared to the untreated control. Pyraclostrobin in combination with metiram @ 1500 g ha-1 reduced plant height by 12% over untreated control. The application of trifloxystrobin + tebuconazole @ 400 g ha-1 gave longer roots, more number of branches and higher total dry matter accumulation. Further, it gave maximum green chilli yield (20.44 t ha-1) with 13% increase over untreated control (15.26 t ha-1).